Enantioselective Degradation of Indoxacarb From Different Commercial Formulations Applied to Tea. Issue 3 (24th January 2015) - Zhang, Yuping; Hu, Deyu; Meng, Xingang; Shi, Qingcai; Li, Pei; Jin, Linhong; Zhang, Kankan; Song, Baoan
Abstract The stereoselective degradation of indoxacarb enriched with (+)‐S‐indoxacarb (S/R:70/30) was investigated in three typical green teas. A convenient and precise chiral method was developed and validated for measuring indoxacarb enantiomers in green tea. The developed method was based on high‐performance liquid chromatography coupled with tandem mass spectrometry using a Chiralpak IC column. The stereoselective degradation of indoxacarb enantiomers showed that the (+)‐S‐enantiomer dissipated faster than the (−)‐R‐enantiomer in all three typical tea farms. However, no enantiomerization was observed after applying pure (+)‐S‐indoxacarb. Residues on tea plant of the active ingredient (+)‐S‐indoxacarb from suspension concentrate (SC) was more persistent than that from emulsifiable concentrate (EC). Chirality 27:262–267, 2015. © 2015 Wiley Periodicals, Inc.